Functional convergence of oxylipin signalling in plants and animals: - Knieper, Madita; Bayer, Joel Niklas; Dietz, Karl-Josef; Viehhauser, Andrea (Biologie in unserer Zeit, 2022)
Oxylipins are oxidation products of membrane lipids. They play important roles as regulators of adaptive and developmental processes. Due to their high reactivity, they can damage cellular structures and cause mutations. The prostaglandins of animals and the cis-12-oxophytodienoic acid of plants are oxylipins. They are enzymatically synthesized by way of different pathways from polyunsaturated fatty acids. This is all the more surprising as they cause similar molecular and physiological effects in animals and plants which indicates a functional convergence.